Effectiveness of Zingiber officinale to reduce inflammation markers and the length of stay of patients with community-acquired pneumonia: An open-label clinical trial - Reviono, Reviono; Hapsari, Brigitta DA.; Sutanto, Yusup S.; Adhiputri, Artrien; Harsini, Harsini; Suryawati, Betty; Marwoto, Marwoto; Syaikhu, Akhmad (Narra Sains Indonesia, 2023)
Examination of the interleukin 6 (IL-6) and procalcitonin levels, and neutrophil-lymphocyte ratio (NLR) might could help to diagnosis and predict the duration of therapy and prognosis of pneumonia cases. Zingiber officinale var rubrum could be used as an adjunct therapy in infectious diseases as it has anti-inflammatory activity. The aim of study was to assess the effect of Z. officinale on levels of IL-6 dan procalcitonin, NLR, and the length of hospitalization of patients with community-acquired pneumonia (CAP). An open-label clinical trial was conducted among CAP cases regardless of the etiology at Dr Moewardi Hospital and Universitas Sebelas Maret Hospital, Surakarta, Indonesia from July to September 2022. A total of 30 inpatient CAP cases were recruited and were randomly divided into two groups: (1) received Z. officinale capsule 300 mg daily for five days in addition to CAP standard therapy; and (2) received CAP standard therapy only, as control group. The data were compared using a paired Student t-test, Chi-squared test, Mann-Whitney test and Wilcoxon signed-rank test as appropriate. In Z. officinale group, the mean difference between post- and pre-treatment as follow: IL-6 level was 9.93 pg/mL, procalcitonin level -471.31 ng/mL, and NLR value -4.01. In control group, the difference was 18.94 pg/mL for IL-6, 339.39 ng/mL for procalcitonin, and 1.56 for NLR. The change of IL-6 was not statistically significant between treatment and control groups with p=0.917. The changes of procalcitonin level and NLR were significant between treatment and control group with p=0.024 and p=0.007, respectively, of which the treatment had better improvement. In addition, our data indicated that the length of stay was not statistically significant between the treatment and control groups (4.13 vs 4.47 days, p=0.361). In conclusion, Z. officinale could reduce serum inflammatory markers such as procalcitonin and NLR but it has little impact in reducing IL-16 level and the length of hospitalization of CAP patients.